EFFECT OF PROBLEM BASED LEARNING MODEL AND MOTIVATION LEARNING ON LEARNING OUTCOMES IN CLASS X SMA SINAR HUSNI - Halimatus Sakdiah Pelawi; Karya Sinulingga (Jurnal Pendidikan Fisika, 2016)
This study aims to determine the effect of problem based learning model towards student learning outcomes, determine the effect learning motivation toward student learning outcomes and determine the effect of interaction between learning model with motivation toward learning outcomes of students. This research is aquasi-experimental, conducted at SMA Swasta Sinar Husni the academic year 2014/2015. Population in the study were all students of class X IPA consisting of 2 classes. Sampling was done by purposive sampling, while the determination of a with drawal carried out by random sample class. This study uses Two group pretest-posttest design. Data analysis using ANOVA two ways. From the study concluded that the results of studying physics students apply problem based learning model is better than the conventional learning models, learning outcomes Physics students who have learning high motivation is better than students with low learning motivation, and there was an interaction between the model of learning by learning motivation on student learning outcomes. That is,the result of learning with problem based learning model is always better than the conventional learning. Likewise, learning outcomes of students who have high motivation to learn will always be better than the learning outcomes of students who have low learning motivation.